Potential of Mesenchymal Stem Cell-Derived Exosomes as a Novel Treatment for Female Infertility Caused by Bacterial Infections - Zohrabi, Marzieh; Dehghan Marvast, Laleh; Izadi, Mahin; Mousavi, Seyed Alireza; Aflatoonian, Behrouz (Frontiers in Microbiology, 2022)
Neisseria gonorrhoeae and Chlamydia trachomatis are the most common causes of bacterial sexually transmitted diseases (STDs) with complications in women, including pelvic inflammatory disease (PID), ectopic pregnancy, and infertility. The main concern with these infections is that 70% of infected women are asymptomatic and these infections ascend to the upper female reproductive tract (FRT). Primary infection in epithelial cells creates a cascade of events that leads to secretion of pro-inflammatory cytokines that stimulate innate immunity. Production of various cytokines is damaging to mucosal barriers, and tissue destruction leads to ciliated epithelial destruction that is associated with tubal scarring and ultimately provides the conditions for infertility. Mesenchymal stem cells (MSCs) are known as tissue specific stem cells with limited self-renewal capacity and the ability to repair damaged tissues in a variety of pathological conditions due to their multipotential differentiation capacity. Moreover, MSCs secrete exosomes that contain bioactive factors such as proteins, lipids, chemokines, enzymes, cytokines, and immunomodulatory factors which have therapeutic properties to enhance recovery activity and modulate immune responses. Experimental studies have shown that local and systemic treatment of MSC-derived exosomes (MSC-Exos) suppresses the destructive immune response due to the delivery of immunomodulatory proteins. Interestingly, some recent data have indicated that MSC-Exos display strong antimicrobial effects, by the secretion of antimicrobial peptides and proteins (AMPs), and increase bacterial clearance by enhancing the phagocytic activity of host immune cells. Considering MSC-Exos can secrete different bioactive factors that can modulate the immune system and prevent infection, exosome therapy is considered as a new therapeutic method in the treatment of inflammatory and microbial diseases. Here we intend to review the possible application of MSC-Exos in female reproductive system bacterial diseases.